Wonder, Horror, Mystery Letters on Cinema and Religion in Malick, Von Trier, and Kieślowski - Meis, Morgan (punctum books, 2021)
Wonder, Horror, Mystery is a dialogue between two friends, both notable arts critics, that takes the form of a series of letters about movies and religion. One of the friends, J.M. Tyree, is a film critic, creative writer, and agnostic, while the other, Morgan Meis, is a philosophy PhD, art critic, and practicing Catholic. The question of cinema is raised here in a spirit of friendly friction that binds the personal with the critical and the spiritual. What is film? What's it for? What does it do? Why do we so intensely love or hate films that dare to broach the subjects of the divine and the diabolical? These questions stimulate further thoughts about life, meaning, philosophy, absurdity, friendship, tragedy, humor, death, and God. The letters focus on three filmmakers who challenged secular assumptions in the late 20th century and early 21st century through various modes of cinematic re-enchantment: Terrence Malick, Lars von Trier, and Krzysztof Kieślowski. The book works backwards in time, giving intensive analysis to Malick's To The Wonder (2012), Von Trier's Antichrist (2009), and Kieślowski's Dekalog (1988), respectively, in each of the book's three sections. Meis and Tyree discuss the filmmakers and films as well as related ideas about philosophy, theology, and film theory in an accessible but illuminating way. The discussion ranges from the shamelessly intellectual to the embarrassingly personal. Spoiler alert: No conclusions are reached either about God or the movies. Nonetheless, it is a fun ride.